Thermal, flow and inclusions analysis of clogging mechanism in continuous casting process - Xiaocheng Liang; Lin Wang; Zhongfei Liu; Zhihui Li; Xudong Luo; Feng Wu; Qichen Yuan; Benjun Cheng (Case Studies in Thermal Engineering)
The ladle shroud is a vital component in the continuous casting process of steelmaking as it supports the production of a wide range of specialty steels. However, it is plagued by a persistent issue of clogging, which not only diminishes the lifetime of the Alumina-Carbon ladle shroud but also severely disrupts the smooth operation of the continuous casting process. Utilizing a numerical simulation technique, the research adopted the method of particle-liquid two-phases coupling, to probe into the clogging mechanism in the ladle shroud from behavior of heat transfer, flow and inclusions. The study indicated that the temperature distribution and flow behavior have a positive effect on the formation of clogging, especially the inclusions. Various factors synergistically contribute on the inner wall, promoting severe clogging at the outlet of the ladle shroud. Finally, a simulation-based clogging mechanism is concluded coupling above factors.